Technical drafting 1 - Cardenas, Elpidio J.; Francisco, Felizardo Y. (Mandaluyong City : National Book Store, 1992)
This book is intended as reference for high school, vocational and technology students in technical drafting/drawing.
Chapter 1 Types of drawing -- Chapter 2 Lettering -- Chapter 3 Drawing instruments, materials and equipment -- Chapter 4 Geometric construction -- Chapter 5 Orthographic projection -- Chapter 6 Dimensioning.
Includes bibliographical references.
Keywords: MECHANICAL DRAWING